ENHANCEMENTS OF GROWTH AND METABOLITES OF INDICA RICE CALLUS (ORYZA SATIVA L. CV. PATHUMTHANI1) USING TiO2 NANOPARTICLES (NANO-TiO2) - S. CHUTIPAIJIT; T. SUTJARITVORAKUL (My University, 2020)
In this research, the effects of a various in concentration of TiO2 nanoparticles (NanoTiO2) were applied to study the cell growth, metabolites and antioxidant responses of callus in indica rice plants. Dose-dependent changes in growth performances, metabolite accumulations and antioxidant activities of callus were found. Mature seeds of indica rice cv. Pathumthani1 were cultured in callus induction medium with different concentrations of Nano-TiO2 (0-600 mg L-1 ). After five weeks of cultivation, the callus formations were measured in fresh weights and dry weights, and the contents of phenolic compounds, flavonoids, and the antioxidant activities of callus extracts were assayed. The Nano-TiO2 induced of fresh weights and dry weights in callus formations when compared with the control treatment (0 mg L-1 Nano-TiO2) were also observed. The flavonoid and phenolic compound contents in rice callus exposed to 400 mg L-1 Nano-TiO2 were 118% and 139%, respectively, higher than rice callus unexposed to Nano-TiO2. Moreover, the antioxidant activities of the callus metabolites studied shows that the percentages of inhibition were up-regulated (84%) when exposed to 400 mg L-1 Nano-TiO2, as a response to the highlevel depletion of the free radicals in metabolites of rice callus. The results obtained from this research showed that the addition of Nano-TiO2 had impacts on the callus growth and metabolite accumulations in rice callus. The results suggested that addition of Nano-TiO2 at appropriate levels could role as an elicitor for biosynthesis of valuable metabolites and antioxidant properties for pharmaceutical applications in further research.
Keywords: Callus; Secondary metabolite; Medicinal Plants and Neuroprotection